Analysis of the Impact of Digitalization of the Financial Sector on Inflation in Indonesia Using the Vector Error Correction Model Method - SETIAWAN, Edi; WIRANDHIKA, Dery; PURWANTI, Desi (Journal of Tourism Economics and Policy, 2024)
Digitalization of the financial sector through non-cash payment instrument means brings many benefits to the Indonesian economy, but also has consequences behind it. This research aims to determine the effect of non-cash payment instruments consisting of electronic money and card payment on inflation in Indonesia using the Vector Error Correction Model (VECM) method. The results of this research show that shocks in the value of electronic money transactions and card payments have a positive effect on inflation in line with the quantity theory of money. This paper concludes that the digitalization of the financial sector gives impacts on inflation in Indonesia, so the government should prepare appropriate policies to balance the positive effects on economic growth and the negative effects on inflation.